Essential University Physics: Volume 1 (4th Edition) Clone

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 13 - Exercises and Problems - Page 248: 80


The proof is below.

Work Step by Step

We first use the distance formula to find: $ A = \sqrt{a^2 + (-b)^2} \\ A = \sqrt{a^2+b^2}$ We now are asked to find the phase constant. To do so, we set the derivative of the equation equal to zero: $0=-asin\omega t - b cos\omega t $ This becomes: $asin \phi = b cos \phi $ $atan \phi = b $ $\phi = tan^{-1}(\frac{b}{a})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.